A representação do lugar social do poeta no Principado de Augusto a partir das Epístolas de Horácio - Silva, Camilla Ferreira Paulino da (2018)
The overall objective of this thesis is to consider the way the epistolary persona set up by Horace in his Epistles relates to his position within Roman society, taking into account the image of the poet as a guide in the process of the establishment of the Augustan Principate. In this way, we seek to analyze the mode through which Horace stands in literary tradition, reflecting on his option to the epistolary genre, its circulation in the Roman world and with which discourses he deals in these works. It is also our aim to discuss how, in the construction of epistolary éthos, Horace presents himself as a model to be followed by the new members of the Roman elite. He appropriates the epistolary scenography to self-represent as someone successful, who, from that point forward, would begin to deliver advice about the best way to behave in the Roman social life. Also, we aim to identify the social role and function that Horace assigns to poets and writers, connecting this to the shaping of a new regime, the Principate, as well as to patronage. For such study, we use, as methodology, the assumptions from Discourse Analysis, as well as the concepts of social place of Michel Pêcheux, representation of Roger Chartier and discoursive practices and éthos of Dominique Maingueneau